PENGARUH GOOD CORPORATE GOVERNANCE, KUALITAS AUDIT, DAN ASIMETRI INFORMASI TERHADAP MANAJEMEN LABA - Donny Prasetyo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to provide empirical evidence about the influence of Good Corporate Governance, audit quality, and information asymmetry on earnings management. The sample of this study is 95 manufacturing companies listed in the Indonesia Stock Exchange in 2015, which were selected through purposive sampling method. This study uses multiple linear regression analysis to identify the influence among variables. The result of this study shows that several mechanisms of Good Corporate Governance, such as institutional ownership, managerial ownership, and audit committee, affect earnings management then variables such as independent commissioner, audit quality, and information asymmetry have no effect on earnings management. Given the mechanism of Good Corporate Governance, the profit management activities can be reduced.Keywords: good corporate governance, audit quality, information asymmetry, earnings management